New approach to the control of particle recycling using divertor pumping in the Large Helical Device. (26th June 2019) - Motojima, G.; Masuzaki, S.; Morisaki, T.; Tanaka, H.; Sakamoto, R.; Murase, T.; Oliver, S.; Kobayashi, M.; Shoji, M.; Tokitani, M.; Tsuchibushi, Y.; Yamada, H.; et al.
Abstract: The effect of the divertor pumping on plasmas has been investigated in the Large Helical Device (LHD). A divertor pump which reaches high pumping speed (67  ±  5 m 3 s −1 in hydrogen) and high pumping capacity (58 000 Pa m 3 in hydrogen) has been developed at LHD. The global particle confinement time ( ), which is expressed as τ p /(1  −   R ), where τ p is the particle confinement time and R is the global recycling coefficient, is used for comparison of operation with and without divertor pumping. After the fueling was stopped, shorter values were obtained in low density plasmas with divertor pumping in comparison with the values without divertor pumping. In this paper, the acceleration of RF wall conditioning by the divertor pumping is also discussed. The effect of the divertor pumping on high density plasmas has been investigated. In high density plasmas obtained by pellet fueling, not only edge density but also core density is reduced by the divertor pumping due to shallower pellet penetration. The control of neutral pressure by the feedback operation of pellet injection and gas puffing likely will be a candidate for the edge density control.